A decision support system for updating and incorporating climate change impacts into rainfall intensity-duration-frequency curves: Review of the stakeholder involvement process. (October 2016) - Sandink, Dan; Simonovic, Slobodan P.; Schardong, Andre; Srivastav, Roshan
Abstract: Stakeholder involvement can serve to increase the quality of decision support systems (DSSs) and increase the perceived legitimacy of DSS outputs. Involving those who are ultimately affected by the outputs of DSSs in system design and development also reflects democratic principles. Importantly, stakeholder involvement can help ensure that the outputs of DSSs are used in decision-making processes. However, DSSs often fail due to poor engagement of stakeholder and end-user communities in the development and design of systems. The stakeholder engagement process applied in the development of the Computerized Tool for the Development of Intensity Duration Frequency Curves under Climate Change described here followed many of the tenants of best practices identified in the literature. While the engagement strategy was generally considered successful, over- and under-representation of some stakeholder groups and long term funding issues were weaknesses in the engagement process. Highlights: This paper reviews stakeholder involvement in the development of a DSS concerning climate change impacts on IDF curves. The DSS project reflected the nature of a "knowledge mobilization" funding mechanism, emphasising practical tool development. The stakeholder involvement process incorporated recommended practices and principles identified in the DSS literature. While generally successful, limited funding constrained stakeholder representativeness and long-term involvement.